Features of the Current State of Students in Regions with High Involvement in the Consequences of Hostilities - Ulyanina, O.A.; Aleksandrova, L.A.; Dmitrieva, S.O. (Socialʹnaâ Psihologiâ i Obŝestvo, 2024)
Objective. The study is aimed on estimation of students' current state in regions with high degrees of involvement in the consequences of hostilities. Background. Research data, mainly foreign ones, indicate a high prevalence of violations of various degrees of severity, from mild adaptation disorders to symptoms of PTSD, in children either living in military conflict zones or having experience related to their involvement into consequences of hostilities. Such students have a great need for targeted psychological assistance. There is still a gap in domestic studies devoted to the analysis of the impact of involvement into consequences of hostilities on minority. Also, specialists are still experiencing deficits in compact tools allowing comprehensive assessment of children current state and their need for psychological assistance. Study design. We studied features of the students' current state in regions highly involved into the consequences of hostilities. using specially developed screening tools designed for students of 9-11 grades.Participants. 646 students in grades 9-11 (36% male, 64% female) living in regions experiencing the impact of events related to hostilities, mainly from Lugansk People's Republic. Measurements. The study is based on a questionnaire developed to assess the current state in adolescents including items assessing a) manifestations of socio-psychological and mental maladaptation in various spheres of life, b) symptoms of posttraumatic stress disorder, c) psychological (personal and social) resources for coping with stress. This part of questionnaire includes lists if features among which student must choose those which fit his/her current state on the base of multiple choice. The questionnaire also contains items assessing the subjective well-being of children in life areas mentioned above by the 10-point Likert scale. The questionnaires were presented electronically, using the AnketologBox platform. Results were analyzed using IBM SPSS 27.0. Results. Results were obtained regarding the prevalence and severity of signs of socio-psychological maladaptation, including PTSD symptoms, and subjective estimation of well-being and psychological resources for coping with stress in students of 9-11 grades. Significant differences were found between students according to the criterion of gender: a significantly higher level of vulnerability of girls compared to boys in the psychophysiological, emotional, behavioral spheres, as well as in relationships with loved ones.Сonclusions. The data analysis allowed us to identify the main features of the current state of students in the regions highly involved in the consequences of hostilities: the presence of severe distress in some children in the psychophysiological, cognitive, emotional, communicative and behavioral spheres, the tendency to decrease the level of well-being in these areas with age in secondary school students, the existence of special risk groups, which include female students of 9-11grades. The proposed diagnostic tool appeared to be sensitive to phenomena under study varying from psychological resources of coping with stress to signs of maladaptation in students living in territories involved into the consequences of hostilities. Цель. Проанализировать особенности актуального состояния обучающихся в регионе с высокой степенью вовлеченности в последствия боевых действий. Контекст и актуальность. Данные исследований, преимущественно зарубежных, свидетельствуют о высокой распространенности у детей, вовлеченных в последствия боевых действий или проживающих в зоне военных конфликтов, нарушений различной степени выраженности, от легких проблем адаптации до симптомов посттравматического стрессового расстройства (далее - ПТСР). Такие дети нуждаются в адресной психологической помощи. Исследований, посвященных анализу влияния, которое оказывает на обучающихся вовлеченность в последствия боевых действий, на сегодня немного, специалисты испытывают дефицит компактных инструментов, позволяющих комплексно оценить актуальное состояние детей и их потребность в психологической помощи. Дизайн исследования. В работе изучаются особенности актуального состояния обучающихся в регионе с высокой степенью вовлеченности в последствия боевых действий. Использован специально разработанный инструмент скрининга, предназначенный для обучающихся 9-11 классов. Участники. 646 обучающихся 9-11 классов (36% мужского, 64% женского пола), преимущественно проживающие на территории Луганской Народной Республики. Методы (инструменты). В основе исследования - анкета, разработанная для оценки актуального состояния ребенка. Она включает пункты, оценивающие: а) проявления социально-психологической и психической дезадаптации, б) симптоматику посттравматического стрессового расстройства, проявляющуюся в различных сферах жизнедеятельности, в) психологические ресурсы ребенка для совладания со стрессом. Опрашиваемым предлагалось выбрать из списка те характеристики, которые они у себя наблюдают, на основе множественного выбора: 0 - признак отсутствует, 1 - признак присутствует. Анкета также содержит пункты, направленные на субъективную оценку ребенком своего благополучия в каждой из перечисленных выше сфер жизнедеятельности, оцениваемые с использованием 10-балльной шкалы Ликерта. Анкета предъявлялась в электронном виде, с использованием платформы AnketologBox (АнкетологБокс). Полученные результаты анализировались с помощью пакета IBM SPSS 27.0. Результаты. Получены результаты о распространенности и выраженности признаков социально-психологической дезадаптации, а также проявлений, которые можно отнести к признакам ПТСР, субъективному благополучию и психологическим ресурсам обучающихся в совладании со стрессом. Обнаружены статистически значимые различия между обучающимися по критерию пола: выявлен значительно более высокий уровень уязвимости девочек по сравнению с мальчиками в психофизиологической, эмоциональной, поведенческой сферах, отношениях с близкими. Основные выводы. Анализ данных позволил выявить основные особенности актуального состояния обучающихся в регионе с высокой степенью вовлеченности в последствия боевых действий: наличие у части подростков выраженного неблагополучия в психофизиологической, когнитивной, эмоциональной, коммуникативной и поведенческой сферах, выраженные различия между мальчиками и девочками в оценках проявлений дезадаптации и признаков ПТСР. Предложенный инструмент скрининга чувствителен в отношении изучаемых феноменов - от психологических ресурсов совладания со стрессом до признаков дезадаптации у обучающихся, проживающих на территориях, вовлеченных в последствия боевых действий.